KEDUDUKAN BILATERAL IMPUNITY AGREEMENT (BIA)/NON SURRENDER AGREEMENT (NSA) TERHADAP STATUTA ROMA 1998 - Wulandari, Ria (TANJUNGPURA LAW JOURNAL, 2018)
The Rome Statute asserts that the ICC has jurisdiction over people (natural person). This affirmation is contained in article 25 (2) stating that persons committing offenses materially included in the ICC jurisdiction shall enter into individual criminal liability. Another article on the non-recognition of impunity is found in the provisions of article 33 of the Rome Statute stating that a person committing crimes covered by the Rome Statute on the basis of superior orders can not escape from criminal responsibility. But the 1998 Rome Statute has weak rules in article 98 paragraph 2 concerning cooperation concerning the release of immunity rights and consent to submit to which the treaty was made because of an existing SOFA agreement prior to the 1998 Rome Statute. The absence of impunity in the Rome Statute of 1998 has provoked a strong reaction from the United States. According to US, this non-impunity provision threatens its citizens, especially US troops who serve as peacekeepers or military cooperation with allies in various parts of the world. Therefore the United States uses the provisions of article 98 paragraph 2 to hold a number of bilateral agreements with various states stating that no citizen shall be an officer or former official, or any military personnel of any party which may be transferred or transferred by another State to the International Criminal Court for any purpose. This agreement became known as the Bilateral Implementation Agreement (BIA). Another term for this agreement is the NonSurrender Agreement (NSA). The BIA / NSA Agreement then becomes contradictory to the objective of the Rome Statute 1998 on impunity repudiation. If the BIA / NSA agreement is justified it will complicate the existence of the International Criminal Court.